2017
DOI: 10.1158/0008-5472.can-17-0671
|View full text |Cite
|
Sign up to set email alerts
|

MetaLnc9 Facilitates Lung Cancer Metastasis via a PGK1-Activated AKT/mTOR Pathway

Abstract: Long noncoding RNAs (lncRNA) participate in carcinogenesis and tumor progression in lung cancer. Here, we report the identification of a lncRNA signature associated with metastasis of non-small cell lung cancer (NSCLC). In particular, elevated expression of LINC00963 (MetaLnc9) in human NSCLC specimens correlated with poor prognosis, promoted migration and invasion of NSCLC cells , and enhanced lung metastasis formation Mechanistic investigations showed that MetaLnc9 interacted with the glycolytic kinase PGK1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
113
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 42 publications
3
113
0
3
Order By: Relevance
“…Overall, the reduction in both metabolites and proteins important for glucose metabolism is striking. Reduced levels of HK2, PGAM1, and PGK1 were detected after APIM-peptide treatment, all of which are glycolytic proteins regulated by, or regulating the PI3K/AKT/mTOR pathway and shown to be important for tumor growth and metastasis (Gao & Han, 2018;Liu et al, 2018;Yu et al, 2017). The AMPK pathway is normally activated by a lowered ATP/AMP ratio and serve to increase glucose uptake in order to maintain cellular ATP levels (Faubert, Vincent, Poffenberger, & Jones, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the reduction in both metabolites and proteins important for glucose metabolism is striking. Reduced levels of HK2, PGAM1, and PGK1 were detected after APIM-peptide treatment, all of which are glycolytic proteins regulated by, or regulating the PI3K/AKT/mTOR pathway and shown to be important for tumor growth and metastasis (Gao & Han, 2018;Liu et al, 2018;Yu et al, 2017). The AMPK pathway is normally activated by a lowered ATP/AMP ratio and serve to increase glucose uptake in order to maintain cellular ATP levels (Faubert, Vincent, Poffenberger, & Jones, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA MEG3 is reported to regulate cisplatin resistance of NSCLC . MetaLnc9 promotes NSCLC metastasis via activation of AKT/mTOR pathway . LncRNA VELUCT regulates NSCLC cell viability .…”
Section: Introductionmentioning
confidence: 99%
“…MetaLnc9, as a metastasis‐related LncRNA, was identified to be obviously up‐regulated in highly metastatic cells and NSCLC tumour tissues, and its expression correlated with distant metastasis and TNM. Yu et al indicated that MetaLnc9 could interact with the glycolytic kinase PGK1 and prevent its ubiquitination in NSCLC cells, resulting in activation of the oncogenic AKT/mTOR signalling pathway …”
Section: Main Molecular Mechanism Of Lncrna To Regulate the Metastasimentioning
confidence: 99%
“…Yu et al indicated that MetaLnc9 could interact with the glycolytic kinase PGK1 and prevent its ubiquitination in NSCLC cells, resulting in activation of the oncogenic AKT/mTOR signalling pathway. 95 NF-κB interacting LncRNA (NKILA), encoded by a gene at chromosome 20q13 just near by the prostate transmembrane protein androgen induced 1 (PMEPA1), 96 was increased by NF-κB in breast cancer. 97 Recently, Lu et al discovered that NKILA expression was negatively associated with tumour metastasis in patients with NSCLC, and the expression of NKILA was regulated through classical TGF-β signal pathway, which subsequently inhibited migration and invasion of NSCLC cells through interfering NF-κB/Snail signal pathway in NSCLC cells.…”
Section: Wnt/β-catenin Signal Pathwaymentioning
confidence: 99%